2012
DOI: 10.4046/trd.2012.73.2.93
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Immediate Diet for Reducing Local Adverse Events of Inhaled Corticosteroid: A Pilot Study

Abstract: BackgroundLocal adverse events associated with inhaled corticosteroid use, including dysphonia, pharyngitis and oral candidiasis, can affect adherence for treatment. 'Mouth rinsing method' has been used for reducing local adverse events, but it cannot ensure complete prevention. The goal of this pilot study was to identify whether the 'immediate diet method' can reduce local adverse events in a limited number of patients.MethodsThe study was conducted in a total of 98 patients, who had been prescribed a medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…Approximately 70% of participants who suffered from LAEs showed improvement after the application of an immediate diet for more than two months. 12 This result was consistent with a previous study that showed no residue remaining in the oesophagus after changing FP-DPI inhalation time to before meals, and hence an improvement of oesophageal candidiasis was observed. 16 The study explained that FP residue deposited in the oesophagus was removed by the passage of food.…”
Section: Local Adverse Eventssupporting
confidence: 93%
See 1 more Smart Citation
“…Approximately 70% of participants who suffered from LAEs showed improvement after the application of an immediate diet for more than two months. 12 This result was consistent with a previous study that showed no residue remaining in the oesophagus after changing FP-DPI inhalation time to before meals, and hence an improvement of oesophageal candidiasis was observed. 16 The study explained that FP residue deposited in the oesophagus was removed by the passage of food.…”
Section: Local Adverse Eventssupporting
confidence: 93%
“…The result from Lee et al showed that the symptoms of LAEs in 14 out of 18 patients (77.8%) were alleviated after applying the immediate diet method. 12 There is no doubt that neither the standard method (mouth rinsing with water) nor immediate diet alone can completely prevent LAEs. So, a new intervention is needed to maximise the efficacy of removing deposited ICS particles in order to minimise the occurrence of its LAEs.…”
Section: Introductionmentioning
confidence: 99%
“…This lends a time-critical aspect to 36 drug delivery since solid particles in the lungs are removed over time by ejection via the mucociliary 37 escalator in the ciliated regions of the lungs or partition into macrophages in the alveoli (Hardy & 38 Chadwick, 2000) and dissolution appears to be the rate-limiting step for the uptake of inhalable drugs 39 (Bur, et al, 2010). If more of a given drug is removed in these manners before itis fully dissolved, a 40 greater dose must be administered and the resultant side effects such as immunosuppression with 1 corticosteroids (Lee, et al, 2012) and hypoalkaemia with salbutamol (Hung, et al, 1999) will have 2 greater impacts on patient health. 3…”
Section: Respiratory Drugs and Drug Delivery 22mentioning
confidence: 99%